Relationship Between Workload_and_Work Fatigue in Cleaning Service Officers at Grandmed Lubuk Pakam Hospital in 2025 - Tarigan, Layari; Ginting, Keleng Ate; Kusuma, Teja; Bakkara, Juwita Delima (JURNAL KESMAS DAN GIZI (JKG), 2025)
Cleaning service personnel play a vital role in maintaining hygiene and sanitation within hospitals as an integral component of healthcare services. Excessive and prolonged workloads can lead to work-related fatigue, which may decrease productivity and elevate the likelihood of occupational accidents. This study aims to examine the relationship between workload and work fatigue among cleaning service staff at Grandmed Lubuk Pakam Hospital in 2025. A quantitative research approach with a cross-sectional design was employed. The study involved all 65 cleaning service workers selected through a total sampling technique. Data were gathered using a structured questionnaire and analyzed using the Chi-square statistical test. The findings revealed that 29 respondents (44.6%) had low workloads, 20 respondents (30.8%) had moderate workloads, and 16 respondents (24.6%) experienced high workloads. Regarding fatigue levels, 23 respondents (35.4%) reported low fatigue, 24 respondents (36.9%) moderate fatigue, and 18 respondents (27.7%) high fatigue. The statistical analysis produced a p-value of 0.030, indicating a significant association between workload and work fatigue. It can be inferred that as workload intensity increases, the likelihood of experiencing fatigue also rises. Hence, effective and ergonomically oriented workload management strategies are essential to minimize fatigue and enhance the overall well-being and performance of cleaning service personnel within the hospital environment.